Structural Factors Contributing to Suicidal Ideation in Iranian Older Adults: A Grounded Theory Approach - Mohammad Rostami; Seyyed Jalal Younesi; Mahshid Foroughan; Farahnaz Mohammadi Shahboulaghi; Seyed Kazem Malakouti (Kerman University of Medical Sciences, 2022)
Introduction: The high rate of complete suicide in older adults on the one hand and the low report of suicidal thoughts by them compared to other groups on the other hand, indicate the importance of suicide in this group. The objective of this study was to explore the structural factors contributing to suicidal ideation in Iranian older adults. Methods: This was a qualitative study using grounded theory approach. The sample included a total of 13 community-dwelling (visiting day-care centers and psychiatric clinics) and institutionalized older adults aged 60 years or above selected using purposive and theoretical sampling methods. The data were collected using in-depth  semi-structured interviews. The data were analyzed using constant comparative method, constant review of the written text of the interviews, field notes, and memo writing via Strauss and Corbin's method. Results: The results indicated 2 main categories including perceived adversities and negative self-concept that were represented in the form of 10 subcategories including having a difficult life, financial strain, retirement, disempowerment, disrupted family, being lonely, being a trouble to others, self-perceived uselessness, lack of control over life, and losing reputation. Conclusion: Suicidal ideation among Iranian older adults occurs in the context of negative life events that can cause significant pain and suffering. The concepts related to family, health, and performance of older adults are especially important in the development of suicidal thoughts due to their cultural significance. Therefore, professionals and policymakers can reduce suicidal ideation in older adults by enriching social interactions, increasing welfare activities, paying more attention to spiritual capacities, and generally reducing the structural challenges in day-care centers and nursing homes.